2000
DOI: 10.1177/107319110000700403
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adolescents' Personality with the NEO PI-R

Abstract: The suitability of the Revised NEO Personality Inventory (NEO PI-R) to assess adolescents' personality traits was investigated in an unselected heterogeneous sample of 469 adolescents aged 12 to 17 years. They were further administered the Hierarchical Personality Inventory for Children (HiPIC) to allow an examination of convergent and discriminant validity. The adult NEO PI-R factor structure proved to be highly replicable in the sample of adolescents, with all facet scales primarily loading on the expected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
1
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 24 publications
10
133
1
9
Order By: Relevance
“…Thus, all participants completed the NEO Five-Factor Inventory (NEO-FFI; Costa and McCrae 1992), a 60-item self-report personality questionnaire that assesses five domains of personality: neuroticism, extraversion, openness, agreeableness, and conscientiousness. This factor structure has been replicated in adolescent samples (Fruyt et al 2000). Go/no-go task-Participants performed a go/no-go task during fMRI scanning (Anderson et al 2005;Schweinsburg et al 2004b).…”
Section: Mood-thementioning
confidence: 92%
“…Thus, all participants completed the NEO Five-Factor Inventory (NEO-FFI; Costa and McCrae 1992), a 60-item self-report personality questionnaire that assesses five domains of personality: neuroticism, extraversion, openness, agreeableness, and conscientiousness. This factor structure has been replicated in adolescent samples (Fruyt et al 2000). Go/no-go task-Participants performed a go/no-go task during fMRI scanning (Anderson et al 2005;Schweinsburg et al 2004b).…”
Section: Mood-thementioning
confidence: 92%
“…This said, several studies have shown that self-reports are reliable when assessing personality (e.g., De Fruyt, Mervielde, Hoekstra, & Rolland, 2000), as well as substance use or other behavioral problems in adolescence (Clark & Winters, 2002;Crowley, Mikulich, Ehlers, Whitmore, & MacDonald, 2001), and hence are useful for clinical practice and research. This, together with guaranteed confidentiality to participants, should contribute to the reliability and validity of these data.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation with the Big Five was examined because three of the five dimensions (i.e., conscientiousness, emotional stability and agreeableness) have been shown to moderately and positively correlate with SJT scores (McDaniel et al 2007) and integrity test scores (Marcus et al 2007). Moreover, the validity and reliability of the scores on the Big Five measure used in this study [i.e., NEO-PI-R (Costa and MacCrae 1992)] has repeatedly been demonstrated (Costa and McCrae 2008), including in samples of adolescents (De Fruyt et al 2000). It is therefore expected that the integrity-based SJT will be correlated to these three Big Five dimensions and that the resulting correlation coefficients will provide a good measure of comparison between the scoring methods.…”
Section: Present Studymentioning
confidence: 99%